Bony avulsion of the supraspinatus origin from the scapular spine - Vochteloo, Anne J. (Springer International Publishing, 2011)
We describe a case of an avulsion of the scapular spine at the origin of the supraspinatus muscle, with successful conservative treatment. An isolated avulsion is rare, as most avulsions occur in combination with other (more severe) injuries such as fractures of the scapula body or neck, coracoid process, glenoid or humerus. These injuries are mostly seen in high-energy trauma cases and need their own specific treatment. One should therefore always rule out concurrent trauma before treating conservatively.